Making neo-nationalist subject in Japan: The intersection of nationalism, jingoism, and populism in the digital age. Issue 1 (March 2022) - Kawamura, Satofumi; Iwabuchi, Koichi
This article considers how digital media communication reconfigures a "neo-nationalist subject" in the Japanese context. A neo-nationalist subject is not the so-called modern national subject that maintains a shared, collective identity as the rationale regulating his or her decisions and behavior, but rather is a fragmented subject that, in view of "the decline of symbolic efficiency, " is open to discourses that others are in effect stealing his or her "enjoyment" ( jouissance ). Starting from an overview of the rise of cyber-nationalism and the popularity of neoliberal authoritarian governance in Japan since the 1990s, we explore how affect-driven digital media environments promoted by a neoliberal economy produce neo-nationalist subjects who attribute responsibility for their dissatisfaction with life to others, and whose self-defensive "drive" functions as the primary support of the culture of hate and modern racism. In this way, we offer an account for the intersection of nationalism, jingoism, and populism in the digital age.